Aplikasi Sistem Broadcast E-mail Pada Website Konferensi International - Limanto, Mulyono Budianto; Gunawan, Ibnu; Dewi, Lily Puspa (Jurnal Infra, 2015)
Technology continues to grow from year to year. One such technology is e-mail that has been developed since 1975 until now. Many people have suffered losses due to missing some information about the conferences in the world and this technology helps to provide all the information about the conferences held in the world to the participants of the conference.This website contains data and the overall schedule of the conference held in the world by using e-mail technology can help participants to obtain various kinds of information and schedules, especially for a conference held in the world, e-mail technology is used to transmit and provide information regularly to the participants of the conference.Â Based on test results, this website can perform the function add an event to provide conference schedule, and update events to change the provider of input errors on the results of the conference and can also send emails automatically and globally to provide information to the participants in accordance with the desired interest while also e-mail is also biased to provide information about the participants kehangusan members so that it can be a reminder to participants.